(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Vaginal discharge is a common gynecological complaint and may be associated with infections or precancerous cervical changes. The Papanicolaou (Pap) smear is a critical screening tool for detecting cervical cytological abnormalities. In developing countries, where cervical cancer screening programs are not well-established, understanding the frequency of abnormal Pap smear findings in women presenting with vaginal discharge is essential. Objective: To determine the frequency and nature of abnormal Pap smear findings among women presenting with vaginal discharge at a tertiary care hospital, with a focus on identifying cytological abnormalities indicative of precancerous and cancerous lesions. Methodology: This cross-sectional study was conducted over six months at a Liaquat University Hospital Hyderabad / Jamshoro in Pakistan. A total of 239 women aged 20 to 50 years with complaints of vaginal discharge lasting 3-6 months were recruited using a non-probability consecutive sampling technique. Exclusion criteria included known genital pathology, diagnosed cervical carcinoma, and vaginal bleeding. Pap smears were collected, preserved in ethanol, and analyzed cytologically. Data were analyzed using SPSS, with statistical significance determined using Chi-square tests (p<0.05). Results: Among the 239 participants, 18.0% had normal Pap smears, while 40.2% exhibited cervicitis, 17.6% dysplasia, 10.9% adenocarcinoma, 7.1% ASCUS, and 10.9% carcinoma in situ. Dysplasia was most prevalent in the 26-35 age group (20.9%), and cervicitis was common in women over 45 years (52.4%). Married women had a higher prevalence of dysplasia (18.5%) and adenocarcinoma (11.3%) compared to unmarried women. Women with prolonged symptoms (>4 months) had higher rates of dysplasia (19.4%) and adenocarcinoma (14.3%). Contraceptive users exhibited higher cervicitis rates (57.8%) but lower carcinoma in situ and adenocarcinoma rates. Conclusion: The high prevalence of cervical cytological abnormalities among women with vaginal discharge underscores the necessity of routine Pap smear screening, particularly for high-risk groups. Increased awareness, accessibility to cervical cancer screening, and HPV vaccination are crucial in reducing the burden of cervical cancer in resource-limited settings. Further research is needed to assess the impact of HPV subtypes and long-term contraceptive use on cervical health.